Optimal Scheduling of Integrated Energy Systems Considering Flexible Demand Response and Carbon Emission-Green Certificate Joint Trading - Cailing ZHANG; Shuang WANG; Shuna GE; Deng PAN; Yan ZHANG; Wei HAN; Wenyan DUAN (Zhongguo dianli)
Under the background of "carbon peaking and carbon neutrality", tapping the demand side resources with effective combination of carbon emission trading and green certificate trading mechanism will help to achieve the development of low-carbon economy in the integrated energy system. For this reason, this paper proposes a low-carbon optimal scheduling strategy for the integrated energy system (IES) considering flexible demand response and laddered carbon emission and green certificate joint trading. Firstly, a waste heat power generation link containing the organic Rankine cycle is introduced at the source side to decouple the constraint of "determining electricity by heat" for CHP, and an integrated demand response model is introduced at the load side, thus forming an flexible demand response model for source and load coordination. Secondly, the principles of carbon emission trading and green certificate trading mechanisms are studied and the correlation between the them is analyzed, and a ladder-type carbon emission and green certificate joint trading mechanism is constructed. Finally, taking into account both the economy and low-carbon performance of the system, a day-ahead low-carbon economic optimization model is constructed with the goal of minimizing the total cost. The simulation results show that the total cost and carbon emissions of the system have decreased by 13.37% and 11.44% respectively after considering the laddered carbon emission and green certificate joint trading mechanism. Compared with the traditional demand response models, the proposed flexible demand response model has reduced the total cost and carbon emissions by 3.87% and 2.85% respectively, effectively achieving economic, flexible, and low-carbon operation of the system.